Facial Soft Tissues Reconstruction Methods After Tumor Resection in Soedarso General Hospital 2017 - 2022 - Jaya, Fidi Bhawana; Setiawan, Doni (Lingkar Studi Bedah Plastik Foundation, 2023)
Introduction: Facial contour deformity is a very challenging problem for aesthetic and reconstructive surgeons. Assessment of facial deformities is important for developing a subsequent reconstruction plan. Various techniques have been described for the repair of tumor-related defects of facial soft tissues. This study aimed to describe methods of Facial Soft Tissue Reconstruction after Tumor Resection at Soedarso General Hospital, West Kalimantan. Method: A retrospective descriptive study using data such as age, gender, type of tumor, size of the defect, and type of reconstruction done, which were collected from medical records of all patients with malignant facial soft tissue tumors who have underwent tissue reconstruction after tumor resection at Soedarso General Hospital, West Kalimantan, between 2017 and 2022. Result: A total of 48 patients were included. 33 patients underwent rotational flap only, 8 patients underwent rotational flap and skin graft, 1 patient underwent transposition flap, 6 patients underwent skin graft. 39 patients had BCC, 7 patients had SCC, 1 patient had MM, 1 patient had Meibom gland Adenocarcinoma. 25 patients were female, 23 patients were male. 41 patients had age 60 years old and older, 7 patients had age younger than 60 years old. 8 patients with defect size larger than 4x4x3 cm, 40 patients with defect size smaller than 4x4x3 cm. Conclusion: Knowledge of distribution patterns of facial soft tissue tumors will help to correctly choose the right options in facial reconstruction. Unawareness can lead to inadequate treatment with serious consequences for the affected patient.